Immunologic findings precede rapid lupus flare after transient steroid therapy - Lu, Rufei (Sci Rep, 2019)
Systemic lupus erythematosus (SLE) flares elicit progressive organ damage, leading to disability and early mortality. This study evaluated clinical and immunologic factors associated with impending flare in the Biomarkers of Lupus Disease study. Autoantibodies and 32 soluble mediators were measured by multiplex assays, immune pathway activation by gene expression module scores, and immune cell subset frequencies and activation states by flow cytometry. After providing baseline samples, participants received transient steroids to suppress disease and were followed until flare. Flare occurred early (within 60 days of baseline) in 21 participants and late (90–165 days) in 13. At baseline, compared to the late flare group, the early flare group had differential gene expression in monocyte, T cell, interferon, and inflammation modules, as well as significantly higher frequencies of activated (aCD11b(+)) neutrophils and monocytes, and activated (CD86(hi)) naïve B cells. Random forest models showed three subgroups of early flare patients, distinguished by greater baseline frequencies of aCD11b(+) monocytes, or CD86(hi) naïve B cells, or both. Increases in these cell populations were the most accurate biomarkers for early flare in this study. These results suggest that SLE flares may arise from an overlapping spectrum of lymphoid and myeloid mechanisms in different patients.